Innovation and Marketing in the Pharmaceutical Industry Emerging Practices, Research, and Policies - Ding, Min.; Ding, Min.; Eliashberg, Jehoshua.; Eliashberg, Jehoshua.; Stremersch, Stefan.; Stremersch, Stefan. (International Series in Quantitative Marketing,, 2014)
The pharmaceutical industry is one of today’s most dynamic and complex industries, involving commercialization of cutting-edge scientific research, a huge web of stakeholders (from investors to doctors), multi-stage supply chains, fierce competition in the race to market, and a challenging regulatory environment.  The stakes are high, with each new product raising the prospect of spectacular success—or failure.  Worldwide revenues are approaching $1 trillion; in the U.S. alone, marketing for pharmaceutical products is, itself, a multi-billion dollar industry.  In this volume, the editors showcase contributions from experts around the world to capture the state of the art in research, analysis, and practice, and covering the full spectrum of topics relating to innovation and marketing, including R&D, promotion, pricing, branding, competitive strategy, and portfolio management.  Chapters include such features as: ·         An extensive  literature review, including coverage of research from fields other than marketing ·         an overview of how practitioners have addressed the topic ·         introduction of relevant analytical tools, such as statistics and ethnographic studies ·         suggestions for further research by scholars and students   The result is a comprehensive, state-of-the-art resource that will be of interest to researchers, policymakers, and practitioners, alike.  .